Parameters for very light jets of cD galaxies - Krause, M; Camenzind, M (New astronomy reviews, 2003)
Recent Chandra X-ray observations of jets in central cluster galaxies show interesting features around the symmetry plane. We have carried out simulations involving bipolar jets, removing the artificial boundary condition at the symmetry plane. We use a very low jet density (IGM/jet ≈10 4) and take into account a decreasing density profile. We find that the jet bow shock undergoes two phases: First a nearly spherical one and second the well-known cigar-shaped one. We propose Cygnus A to be in a transition phase, showing clear signs from both phases. Due to inward growing of Kelvin Helmholtz instabilities (KHI) between cocoon and shocked IGM, mass entrainment is observed predominantly in the symmetry plane. We propose this mechanism to produce some of the so far enigmatic X-ray features in the symmetry plane in Cygnus A.